KARAKTERISTIK MORFOLOGIS DAN ANATOMIS DAUN TUMBUHAN TINGKAT SEMAI PADA PAPARAN CAHAYA BERBEDA DI HUTAN PENDIDIKAN FAKULTAS KEHUTANAN UNIVERSITAS MULAWARMAN - Karyati Kasiman; Dyna Syarofa Ramadhani; Muhammad Syafrudin (Fakultas Kehutanan Universitas Mulawarman, 2017)
The light intensity influences to morphological and anatomical characteristics of plant leaves in the process of plant growth. The objective of this study was to know morphological and anatomical characteristics of the seedling plant leaves in the different light intensities. The study was conducted in Education Forest of Forestry Faculty of Mulawarman University. The three study sites were selected to represent heavy, moderate, and little light intensities, respectively. The vegetation survey was done in 20 quadrants of 2 m × 2 m in three different light intensities. The analyses of morphological and anatomical characteristics were done to leaves of most five dominant species based on Important Value Index (IVI) in each study site. The morphological characteristics of seedling leaves in heavy, moderate, and little light intensities were leaves length of 13.4 cm, 13.9 cm, and 16.5 cm; leaves wide of 5.0 cm, 5.4 cm, and 6.1 cm, and leaves thick of 0.09 mm; 0.08 mm, and 0.06 mm, respectively. While anatomical characteristic of chlorophyll content of seedling leaves in heavy, moderate, and little light intensities were 45.5%, 46.0%, and 42.7%.